Teachers' Voices on the use of ICT tools in teaching English at Senior High School - Raden Roro Priscylla Dwi Cahyani; Tiara Aprillia; Wulandari; Sufy Rizky; Disti Apriani; Erwin Pohan (CV. Kalimasada Group Profesional, 2025)
This study examines teachers' experiences in utilizing Information and Communication Technology (ICT) tools for English language teaching at the senior high school level. In the digital era, ICT integration has become essential to enhance teaching effectiveness, foster student engagement, and support autonomous learning. Through a qualitative approach, interviews were conducted with two English teachers from SMA Negeri 2 Tanjungpinang to explore the benefits and challenges of ICT implementation. The findings highlight that ICT tools, including PowerPoint, Learning Management Systems (LMS), and collaborative platforms, significantly improve the teaching-learning process. These tools facilitate engaging multimedia-based instruction, effective assessment methods, and interactive learning environments. Applications like Elsa Speak also enhance students' speaking and pronunciation skills. Despite these advantages, several challenges were identified, such as limited technological infrastructure, insufficient teacher training, and inflexible features of certain platforms. For example, some quiz systems do not accept alternative answers, leading to inefficiencies. This study emphasizes the need for infrastructure improvements, continuous professional development for teachers, and the development of more adaptive ICT tools. These efforts are crucial to overcoming existing barriers and optimizing ICT integration in education. The findings provide valuable insights for policymakers, curriculum developers, and educators to enhance the quality of English language teaching and ensure equitable access to technology in learning.